(untitled) (Nexus International Journal of Science and Education, 2024)
This descriptive-correlational research study explores the implementation of Brigada Pagbasa, a reading initiative, and its relationship with students’ reading advancement in a school district in Davao Oriental, Philippines. The study found that Brigada Pagbasa was extensively implemented across its four domains: collaborative management, community volunteerism, shared accountability, and people empowerment. Reading advancement was moderate, assessed through alphabetic fluency, word and pattern recognition, intermediate reading, and advanced reading. Multiple regression analysis indicated that the four domains of Brigada Pagbasa significantly influenced reading advancement. The study discusses implications for policy and practice, suggesting that future research should investigate the specific mechanisms through which these domains impact reading outcomes and identify best practices for implementation.